SEBARAN SPASIAL SUHU PERMUKAAN LAUT DAN KLOROFIL-a PADA DAERAH PENANGKAPAN IKAN CAKALANG (Katsuwonus pelamis) DI PERAIRAN SUMATERA BARAT - Nofrita, Nofrita; Nurdin, Jabang; Fitra, Ramadani; Savitri, Vivi; Bintari, Andhani N.; Saniyyah, Jauharah; Sumartin, Harry (Universitas Andalas, 2024)
West Sumatra waters is one of the potential fishing grounds for skipjack tuna. Oceanographic factors become the primary factors that limit the distribution and abundance of fish. This research aims to understand the spatial distribution of chlorophyll-a and sea surface temperature, and their utility for estimating potential fishing areas in the waters of West Sumatra. The data collection of fish catching area coordinates was carried out from June to July 2023. The sea surface temperature and chlorophyll-a data were downloaded from the website http://oceancolor.gsfc.nasa.gov. The research results found that the sea surface temperature in the waters of West Sumatra from June to July 2023 ranged between 27.9°C to 33.5°C, with an average of 30.25°C, while the chlorophyll-a ranged from 0.014 mg/m3 to 1.684 mg/m3, with an average value of 0.9515 mg/m3. The potential fishing areas for Skipjack Tuna identified during the research in the waters of West Sumatra were around Siberut Island in the Mentawai Islands, at the coordinates of 98°98’15.43